NEW CREATION AND LIFE TRANSFORMATION IN CHRIST: An Exegetical Study of en Christo in 2 Corinthians 5:17 - Susanto Dwiraharjo; Lim Jae Young (QUAERENS: Journal of Theology and Christianity Studies, 2025)
The inconsistency between Christian confession and daily conduct calls for a biblically grounded understanding of life transformation. This study examines the meaning of the phrase en Christo (“in Christ”) in 2 Corinthians 5:17 using grammatical and lexical exegesis. The analysis shows that the phrase denotes not merely a positional union with Christ but a dynamic, participatory relationship resulting in kainē ktisis—a new creation. The perfect tense of gegonen (“has become”) indicates that the new reality has already arrived, while the aorist parelthen (“passed away”) marks a decisive break with the old. This transformation is not superficial moral improvement but a radical, divinely wrought renewal that affects identity, character, and daily practice. The study contributes to practical theology by grounding life renewal in textual analysis rather than abstract doctrine.